A multi-model approach to Saint-Venant equations: a stability study by LMIs - Martins, Valérie Santos dos; Rodrigues, Mickael; Diagne, Mamadou (Zielona Góra: Uniwersytet Zielonogórski)
This paper deals with the stability study of the nonlinear Saint-Venant Partial Differential Equation (PDE). The proposed approach is based on the multi-model concept which takes into account some Linear Time Invariant (LTI) models defined around a set of operating points.
Keywords: Saint-Venant equation; multi-model; LMIs; infinite dimensional system; exponential stability; strongly ontinuous semigroup; internal model boundary control